Estuaries and Coastal Zones Dynamics and Response to Environmental Changes - Pan, Jiayi; Devlin, Adam (IntechOpen, 2020)
Estuaries and their surrounding wetland regions are among the most productive ecosystems in the world, with more than half of humanity inhabiting their shores. Anthropogenic factors make estuaries highly susceptible to ecosystem degradation. Coastal waters are closely connected with human activity, and their dynamic processes may greatly affect coastal environments. This book provides a compendium of studies on estuarine dynamics, river plumes, and coastal water dynamics, studies that have investigated the changes in estuarine and coastal zones in response to sea-level rise and other environmental factors, and policy and management strategies to ensure the health and economy of coastal zones. This book aims to display novel frontiers in these fields and may help to inspire in-depth studies in the future.